2015
DOI: 10.1002/cncr.29619
|View full text |Cite
|
Sign up to set email alerts
|

Can hepatic resection provide a long‐term cure for patients with intrahepatic cholangiocarcinoma?

Abstract: BACKGROUND: A patient can be considered statistically cured from a specific disease when their mortality rate returns to the same level as that of the general population. In the current study, the authors sought to assess the probability of being statistically cured from intrahepatic cholangiocarcinoma (ICC) by hepatic resection. METHODS: A total of 584 patients who underwent surgery with curative intent for ICC between 1990 and 2013 at 1 of 12 participating institutions were identified. A nonmixture cure mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 35 publications
1
82
0
Order By: Relevance
“…Operative intervention for ICC can be technically challenging and complex. Frequently patients present with advanced disease that requires a major hepatic resection . In some instances, the ICC mass may involve a major vascular structure such as the PV or ICC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Operative intervention for ICC can be technically challenging and complex. Frequently patients present with advanced disease that requires a major hepatic resection . In some instances, the ICC mass may involve a major vascular structure such as the PV or ICC.…”
Section: Discussionmentioning
confidence: 99%
“…While patients with unresectable disease have a 5‐year survival of 5‐10%, 5‐year survival among patients after curative surgery ranges from 35% to 50% . Spolverato et al have even suggested that true “cure” may be possible in approximately 10% of patients following surgical resection . Several prognostic factors including tumor multi‐centricity, poor differentiation, lymphatic metastasis, and surgical margin status may explain the heterogeneity in prognosis …”
Section: Introductionmentioning
confidence: 99%
“…In a recent multicenter study enrolling 584 patients who underwent resection for ICC, the overall probability of cure was 9.7% (95% CI, 6.1%-13.4%), which was higher (25.8%) in patients with single, well-differentiated small (≤ 5 cm) lesions and without vascular/periductal invasion and node metastases [65] . Even in selected candidates with younger Page 10 of 36 age and earlier-stage lesions, R0 resection can only be achieved in less than 30% of patients [66] .…”
Section: Surgical Resectionmentioning
confidence: 98%
“…These data serve to emphasize the marked differences in both chances of cure and the time to assuming a 99 % level of cure confidence. In general, results reported herein for patients with extrahepatic biliary tract cancers were slightly better than the 10 % overall chance of cure for patients undergoing surgery for intrahepatic cholangiocarcinoma (ICC) [22]. Moreover, when patients with ICC were compared to patients with PHCC or GBC, the cure probability was 25.8 versus 30.1 %, respectively, among patients with favorable prognostic factors.…”
Section: Discussionmentioning
confidence: 82%
“…In a separate study, investigators evaluated the cure fraction of patients with liver and pancreatic cancers [21]. Our own group has also previously assessed the probability of being statistically cured from intrahepatic cholangiocarcinoma among a large cohort of patients undergoing curative-intent surgery [22]. However, the chance of statistical cure among patients with extrahepatic biliary tract cancers remains undefined.…”
Section: Introductionmentioning
confidence: 99%